(untitled) (Grande Medical Journal, 2025)
Background Hypospadias is one of the commonest congenital penile deformities with wide range of problems. There is wide range of complications associated with hypospadias repair worldwide. The main purpose of this study aimed to evaluate the geographical distribution, patterns of hypospadias, and outcome of hypospadias repair. Method A retrospective study of all patients who underwent hypospadias repair at a single unit of Kanti Children’s Hospital between Baisakh 2079 and Chaitra 2080 was performed. Demographic data, age at surgery, variant of hypospadias, and postoperative outcomes were analyzed. Result A total of 103 patients were studied, among those patients the mean age at surgery was 4.99 years, and the 38(36.82%) were of school-going age and from the Terai region of Nepal (60.19%). 41 (39.8%) patients had proximal hypospadias, 17 (16.5%) had mid penile and distal hypospadias was seen in 43 patient (41.7%). Urethroplasty was performed in 80 (77.6%) patients, and 23 patients (22.33%) underwent orthoplasty. Periurethral leakage 18(17.4%) followed by thrombophlebitis 10(9.7%) was seen immediately in postoperative period. Urethro-cutaneous fistula 33(41.3%) was the most common complication in urethroplasty. Conclusion This study demonstrated that fistulas were the most common, irrespective of the type of surgical repair, while wound dehiscence the least common. Meatal stenosis was one of the risk factor for urethro-cutaneous fistula which was seen in this study.